The effects of COVID-19 on self-harm in UK prisons. (June 2021) - Hewson, Thomas; Green, Russell; Shepherd, Andrew; Hard, Jake; Shaw, Jennifer
Abstract : Self-harm is a major international public health concern and is especially prevalent among prisoners. In this editorial, we explore recent trends in prisoner self-harm during the coronavirus lockdown, and consider strategies for improving the prevention and management of self-harm in prisons as we emerge from the pandemic.